2022
DOI: 10.3390/biomedicines10112792
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of Plant Extract-Synthesized Silver Nanoparticles

Abstract: Silver nanoparticles (AgNPs) have attracted a lot of interest directed towards biomedical applications due in part to their outstanding anti-microbial activities. However, there have been many health-impacting concerns about their traditional synthesis methods, i.e., the chemical and physical methods. Chemical methods are commonly used and contribute to the overall toxicity of the AgNPs, while the main disadvantages of physical synthesis include high production costs and high energy consumption. The biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 154 publications
(211 reference statements)
1
32
0
Order By: Relevance
“…Ag NPs can be prepared by eco-friendly techniques using plant extracts, and biological or microbial agents instead of highly toxic reducing chemicals to meet the strict requirements in bio-applications. 16 Zinc oxide nanoparticles (ZnO NPs) are recognized as a bio-safe nanomaterial applied in biology and medicine with some interesting possibilities such as antitumor, antimicrobial, antifungal and anti-inammatory activities, wound healing ability, antidiabetic properties, etc. 17,18 It was reported that the minimum inhibitory concentration of biosynthesized Ag and ZnO NPs against various bacterial strains varied in the ranges of 31.25 O 62.5 mg L −1 and 440 O 854 mg L −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Ag NPs can be prepared by eco-friendly techniques using plant extracts, and biological or microbial agents instead of highly toxic reducing chemicals to meet the strict requirements in bio-applications. 16 Zinc oxide nanoparticles (ZnO NPs) are recognized as a bio-safe nanomaterial applied in biology and medicine with some interesting possibilities such as antitumor, antimicrobial, antifungal and anti-inammatory activities, wound healing ability, antidiabetic properties, etc. 17,18 It was reported that the minimum inhibitory concentration of biosynthesized Ag and ZnO NPs against various bacterial strains varied in the ranges of 31.25 O 62.5 mg L −1 and 440 O 854 mg L −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nanoparticles produced by green synthesis are biocompatible because of the involvement of biomolecules as reducing agents. Furthermore, green synthesis methods are simple, easy, cost-effective, and environmentally friendly [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, published articles on the effects of AdSP on cell behavior are mainly focused on the inhibition of tumor cell proliferation, anti-angiogenesis, enhancement of hematopoietic stem cells, etc. [ 12 , 13 , 14 ]. Only one study focuses on the effects of AdSP on the behavior of neural stem cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%